Increasing Tau 4R Tau Levels Exacerbates Hippocampal Tau Hyperphosphorylation in the hTau Model of Tauopathy but Also Tau Dephosphorylation Following Acute Systemic Inflammation - Barron, Matthew R.; Gartlon, Jane; Dawson, Lee A.; Atkinson, Peter J.; Pardon, Marie-Christine (Frontiers in Immunology, 2020)
Inflammation is considered a mechanistic driver of Alzheimer’s disease, thought to increase tau phosphorylation, the first step to the formation of neurofibrillary tangles (NFTs). To further understand how inflammation impacts the development of tau pathology, we used (hTau) mice which express all 6, non-mutated, human tau isoforms, but with an altered ratio of tau isoforms favouring 3R tau due to the concomitant loss of murine tau (mTau) that is predominantly 4R. Such imbalance pattern has been related to susceptibility to NFTs formation, but whether or not this also affects susceptibility to systemic inflammation and related changes in tau phosphorylation is not known. To reduce the predominance of 3R tau by increasing 4R tau availability, we bred hTau mice on a heterozygous mTau background and compared the impact of systemic inflammation induced by lipopolysaccharide (LPS) in hTau mice hetero- or homozygous mTau knockout. 3-month-male wild-type (Wt), mTau+/-, mTau-/-, hTau/mTau+/- and hTau/mTau-/- mice were administered 100, 250 or 330µg/kg of LPS or its vehicle PBS (i.v., n=8-9/group). Sickness behaviour, reflected by behavioural suppression in the spontaneous alternation task, hippocampal tau phosphorylation, measured by western immunoblotting, and circulating cytokine levels were quantified 4h after LPS administration. The persistence of the LPS effects (250µg/kg) on these measures, and food burrowing behaviour, was assessed at 24h post-inoculation in Wt, mTau+/- and hTau/mTau+/- mice (n=9-10/group). In the absence of immune stimulation, increasing 4R tau levels in hTau/mTau+/- exacerbated pS202 and pS396/404 tau phosphorylation, without altering total tau levels or worsening early behavioural perturbations characteristic of hTau/mTau-/- mice. We also show for the first time, that modulating 4R tau levels in hTau mice affects the response to systemic inflammation. Behaviour was suppressed in all genotypes 4h following LPS administration but hTau/mTau+/- exhibited more severe sickness behaviour at the 100µg/kg dose, and a milder behavioural and cytokine response than hTau/mTau-/- mice at the 330µg/kg dose. All LPS doses decreased tau phosphorylation at both epitopes in hTau/mTau+/- mice, but pS202 levels were selectively reduced at the 100µg/kg dose in hTau/mTau-/- mice. Behavioural suppression and decreased tau phosphorylation persisted at 24h following LPS administration in hTau/mTau+/- mice.